How do sources of traditional legitimacy constrain popular uprisings? The case of the Kingdom of Swaziland. (23rd February 2019) - Møller, Fenja Søndergaard
ABSTRACT: Research concerning authoritarian stability and peace usually investigates co-optation and repression. Recently, several studies argue that traditional legitimacy is also important for stability in monarchies. However, existing research rarely considers how legitimacy constrains rebellions and help the royal family to stay in power. Hence, this article explores the causal links between sources of traditional legitimacy and absence of uprisings. The study investigates the relationship with a case study of the Kingdom of Swaziland. In line with my expectations, I find a causal relationship between sources of traditional legitimacy and absence of popular uprisings. First, the royal family actively uses traditional legitimacy to justify their rule. Second, the Afrobarometer indicates that the Swazi people trust the King more than citizens in other African countries trust their head of state. Third, opposition actors have limited opportunities to mobilize the broader population against the monarchy. Fourth, traditional legitimacy dampens ongoing protests and thereby hinders their escalation into popular uprisings or political violence. Repression is clearly an important explanation for limited rebellion in Swaziland, but this article shows that also traditional legitimacy sources play a role.